(untitled) (Issues in Social and Environmental Accounting (ISEA), 2013)
The rationale behind the establishment of Islamic organisations globally is based on the precept that Islamic organisations’ practices are conducted in accordance with the strict values and principles of Syariah. In line with this premise, the Corporate Social Responsibility (CSR) policies and practices of Islamic organisations should be underpinned by Islamic laws and principles as revealed in the Qur’an and the Sunnah. Drawing on the doctrine of Maqasid al Syariah and the concept of Maslahah, this study proposes an Islamic CSR (i-CSR) conceptual framework that will align the CSR policies and practices of Islamic organisations with the principles and values of Islam. The two conceptions are integrated with the CSR dimensions resulting in the prioritization of CSR practices based on Syariah principles. This study provides a structured approach to CSR policies and practices for Islamic organisations to ensure full compliance with Islamic principles. Such a conceptual framework would be of interest to Islamic organisations worldwide and regulatory authorities in countries that are hosts to Islamic organisations to improve CSR policies, practices and disclosure on the part of Islamic organisations